2009
DOI: 10.1007/s00382-008-0523-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of salinity in the decadal variability of the North Atlantic meridional overturning circulation

Abstract: An OGCM hindcast is used to investigate the linkages between North Atlantic Ocean salinity and circulation changes during . The focus is on the eastern subpolar region consisting of the Irminger Sea and the eastern North Atlantic where a careful assessment shows that the simulated interannual to decadal salinity changes in the upper 1500 m reproduce well those derived from the available record of hydrographic measurements. In the model, the variability of the Atlantic meridional overturning circulation (MOC) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 59 publications
3
27
0
Order By: Relevance
“…In NCAR and MPI-M, surface fluxes gain importance in the FW budget. The high correlation between FW content changes and FW convergence is consistent with hindcast simulations (e.g., Frankignoul et al 2009) and the preindustrial control run of another climate model (Wu and Wood 2008). Direct observations of oceanic full-depth circulation are too rare to evaluate FW convergence to the subpolar gyre and check whether this result is realistic.…”
Section: Discussionsupporting
confidence: 80%
“…In NCAR and MPI-M, surface fluxes gain importance in the FW budget. The high correlation between FW content changes and FW convergence is consistent with hindcast simulations (e.g., Frankignoul et al 2009) and the preindustrial control run of another climate model (Wu and Wood 2008). Direct observations of oceanic full-depth circulation are too rare to evaluate FW convergence to the subpolar gyre and check whether this result is realistic.…”
Section: Discussionsupporting
confidence: 80%
“…Thierry et al (2007); for the changes in eastern Atlantic, cf. Hä tun et al (2005) and Frankignoul et al (2009), mostly from model studies]. Advective signals in the upper layer are also detected mostly along the path of the NAC and its branches in the subpolar gyre from the salinity and temperature variability of 10 yr or less [Belkin et al (1998) for the Great Salinity Anomalies (GSA); Reverdin et al (1997); Holliday et al (2008)], and have also been commented on in model studies by Hä kkinen (1993,2002).…”
Section: Introductionmentioning
confidence: 83%
“…This hints that, on these decadal time series, surface changes are indicative of large advective changes associated with the ebbing and flowing of more subtropical water to the northern latitudes. Model studies for the late 1950s to the early 2002 period (Hä tun et al 2005;Frankignoul et al 2009) reinforce this dominant advective source of the variability and relate the recent change to gyre intensity and shape changes. This is also suggested in the long hydrographic time series (Holliday et al 2008).…”
Section: Introductionmentioning
confidence: 92%
“…In present-day climate conditions, it has been shown that the variability of deep convection in the Labrador Sea is largely driven by the North Atlantic Oscillation (NAO); through its influence on the wintertime buoyancy loss to the atmosphere (Latif et al 2006;Frankignoul et al 2009) (with positive NAO conditions promoting convective mixing). Furthermore, the transport of freshwater from the Fram Strait along the Greenland coast into the Labrador Sea is also known as a contributing factor to deep convection (Holland et al 2001;Jungclaus et al 2005;Koenigk et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the transport of freshwater from the Fram Strait along the Greenland coast into the Labrador Sea is also known as a contributing factor to deep convection (Holland et al 2001;Jungclaus et al 2005;Koenigk et al 2006). In a warmer climate, however, the deep convective mixing that occurs in the Labrador Sea and the Irminger Sea is expected to decline due to a warming and a freshening of the surface (Latif et al 2006;Deshayes et al 2007; Koenigk et al 2007;Frankignoul et al 2009). …”
Section: Introductionmentioning
confidence: 99%